2015
DOI: 10.1097/sla.0000000000000832
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Shifting Patterns in Quality of Life After Distal Subtotal Gastrectomy

Abstract: Persistent QoL deterioration after distal subtotal gastrectomy is primarily due to financial difficulties, eating restrictions, and body image concerns. Preoperative-based interpretation of postoperative QoL may exaggerate the persistency of reduced QoL and conceal on-going QoL deterioration after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…In addition, the anxiety score was highest at 1 year after surgery, and decreased to the preoperative level 5 years after gastrectomy [1819]. Patients' worsened body image did not return to preoperative levels during the 5 years after gastrectomy [20]. In our study, changes in the proportions of patients reporting poor QoL in relation to emotional functioning, anxiety scale, and body image items were similar to those of previous studies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, the anxiety score was highest at 1 year after surgery, and decreased to the preoperative level 5 years after gastrectomy [1819]. Patients' worsened body image did not return to preoperative levels during the 5 years after gastrectomy [20]. In our study, changes in the proportions of patients reporting poor QoL in relation to emotional functioning, anxiety scale, and body image items were similar to those of previous studies.…”
Section: Discussionsupporting
confidence: 86%
“…Although the preoperative QoL was not altered by surgery, it might represent a patient's QoL after the diagnosis of gastric cancer. A preoperative-based interpretation of postoperative change in QoL may not only exaggerate the persistence of a decreased QoL but also conceal ongoing QoL deterioration after surgery [20]. However, obtaining data regarding patient QoL before the diagnosis of gastric cancer is not feasible in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The results further showed additional benefits of fewer overall and minor complications, shorter length-of-stay (Weighted Mean Difference -3.6 days) and less blood loss [69]. Also, a longer operation time and lower number of harvested Table 2) [69][70][71][72][73]. The general conclusion of these studies is that the laparoscopic approach offers improved recovery after surgery at no compromise of morbidity and mortality.…”
Section: Laparoscopic Surgerymentioning
confidence: 84%
“…Other studies to date have been mostly in Asian populations. As mentioned previously, there are important differences between Eastern and Western gastric cancer patients and their treatment [71][72][73]. One other Western study also found profound impact on HRQoL immediately after surgery and showed some improvement over the next six months [74].…”
Section: Health Related Quality Of Life After Gastric Cancer Surgerymentioning
confidence: 92%
See 1 more Smart Citation